Mitoprotective Effects of Centella asiatica (L.) Urb.: Anti-Inflammatory and Neuroprotective Opportunities in Neurodegenerative Disease - Wong, Jia Hui; Barron, Anna M.; Abdullah, Jafri Malin (Frontiers in Pharmacology, 2021)
Natural products remain a crucial source of drug discovery for accessible and affordable solutions for healthy aging. Centella asiatica (L.) Urb. (CA) is an important medicinal plant with a wide range of ethnomedicinal uses. Past in vivo and in vitro studies have shown that the plant extract and its key components, such as asiatic acid, asiaticoside, madecassic acid and madecassoside, exhibit a range of anti-inflammatory, neuroprotective, and cognitive benefits mechanistically linked to mitoprotective and antioxidant properties of the plant. Mitochondrial dysfunction and oxidative stress are key drivers of aging and neurodegenerative disease, including Alzheimer’s disease and Parkinson’s disease. Here we appraise the growing body of evidence that the mitoprotective and antioxidative effects of CA may potentially be harnessed for the treatment of brain aging and neurodegenerative disease.